The Moderating Role of Empathic Leadership in Job Crafting and Employee Engagement Among Millennial Workers Under Job Stress - Ferdinan, Bernardus Aris; Nugroho, Robertus Adi; Pangemana, Jonathan Edward (Journal of Leadership in Organizations, 2025)
Introduction/Main Objectives: This study aims to examine the role of job stress and employee engagement of millennial workers mediated by job crafting and moderated by empathetic leadership. Background Problems: Leadership is one of the factors that will affect workforce management. The right leadership is seen to help reduce job stress and increase employee engagement. Novelty: Many studies have attempted to examine the relationship between job stress and employee engagement. Gap research, based on the inconsistency of the results of the research that has been done, is the basis for this study. The existing inconsistency makes this research add the role of job crafting and empathic leadership. Research Methods: This study involved 304 non-managerial workers in Surabaya City, Indonesia, who belong to the Millennial generation category. Finding/Results: The results obtained are that job stress has no effect on job crafting. Empathetic leadership moderates job stress and job crafting. Job crafting does not affect employee engagement. Job stress has a negative effect on employee engagement. Job crafting does not mediate the relationship between job stress and employee engagement, and empathetic leadership moderates the relationship between job stress and employee engagement. Conclusion: Practical implications, leaders need to determine the right leadership model according to the context of workers.